Aphasia rehabilitation: a narrative review of adjuvant techniques - Harnish, Stacy M.; Jewell, Courtney C.; Freitag, Natalie G.; Terry, Grace E.; Anderson, Gillian I. (Frontiers in Human Neuroscience, 2025)
Adjuvant techniques, or strategies that may be employed alongside language therapy for individuals with aphasia, are increasingly gaining attention for their ability to promote an enhanced brain environment for neuroplasticity. This narrative review describes active ingredients, mechanisms of action, potential modulating factors and evidence for efficacy of non-invasive brain stimulation techniques, such as transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS); aerobic exercise; intention treatment; and pharmacotherapies, including monoaminergic, cholinergic, glutaminergic, and nootropic medications that have been used in concert with language therapy for aphasia.